Strategi Adaptasi Guru dalam Implementasi Kurikulum Merdeka di SMAN 1 MONTASIK - Nisa, Khairun; Nurdin, Ibnu Phonna (INDO PUBLISHING, 2026)
Since 2021, the government has begun introducing the Merdeka Curriculum. Implementing the independent curriculum requires adaptation from both teachers and students. The purpose of this study is to identify strategies that teachers can use to adapt to the independent curriculum, as well as the problems faced by teachers during its implementation at SMA Negeri 1 Montasik. This study uses Talcott Parsons' theory of functional structure, namely the AGIL theory. The author employs a qualitative descriptive research approach, which is a type of field research. Documentation, interviews, and observations were used to collect data. The results of this study indicate that the implementation of the independent curriculum at SMA Negeri 1 Montasik still requires adaptation strategies among teachers. As for the necessary adaptations, they are in the use of technology, adaptation to learning methods, and social adaptation. In order for a program to be successfully implemented, the teaching methods used must support this Merdeka Curriculum program, student involvement in the learning process, and evaluation of student learning progress. The involvement of the government, parents, teachers, students, and the surrounding community is highly needed in the implementation process of this Merdeka Curriculum. To maintain this Merdeka Curriculum program, it is necessary to uphold the rules, values, and norms that have been agreed upon together. Teachers' adaptation strategies in implementing the Merdeka Curriculum at SMA Negeri 1 Montasik are still not optimal because teachers are still experiencing several obstacles.